2008
DOI: 10.1038/eye.2008.161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phacoemulsification surgery on progression of idiopathic epiretinal membrane

Abstract: Purpose To examine whether or not phacoemulsification surgery accelerates the progression of idiopathic epiretinal membrane (ERM) by measuring the degree of ERM. Methods Forty-three consecutive eyes with idiopathic ERM that underwent phacoemulsification surgery were recruited; 41 consecutive eyes with ERM that did not undergo surgery served as controls. Foveal thickness and macular volume were measured using optical coherence tomography at 3 days after surgery (baseline), and at 3, 6, and 12 months after basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
15
3
1
Order By: Relevance
“…[6][7][8][9][10][11][12] However, in our study, these were not found to be associated with VMIA formation (Table 2). It is possible that our study size was too small to have enough statistical power to detect categorized risk factors for VMIA such as percentage of cataract operation or PRP for an infrequent complication like VMIA.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] However, in our study, these were not found to be associated with VMIA formation (Table 2). It is possible that our study size was too small to have enough statistical power to detect categorized risk factors for VMIA such as percentage of cataract operation or PRP for an infrequent complication like VMIA.…”
Section: Discussioncontrasting
confidence: 46%
“…Vitreomacular interface abnormality (VMIA) such as epiretinal membrane (ERM) or vitreomacular traction (VMT) is one of the most common complications associated with ocular surgical procedures. It is well known that ocular surgeries such as cataract extraction, [6][7][8][9][10][11] surgery for retinal detachment, 12,13 laser photocoagulation 7,12 and retinal cryopexy procedures 12,14 are all associated with an increased incidence of ERM formation. As diabetic retinopathy and DME usually run a chronic and recurrent course, repeated intravitreal injection is often necessary to maintain the edema-suppressing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Tsilimbaris and colleagues found that mean foveal thickness values demonstrated a statistically significant increase in patients with pre‐existing epiretinal membrane six months after cataract surgery. Hayashi and Hayashi demonstrated that the degree of epiretinal membrane, measured as the foveal thickness and macular volume, increased gradually during 12 months in eyes that underwent uneventful phacoemulsification surgery as well as in eyes that did not undergo surgery, thereby suggesting that the progression noticed following cataract surgery might also be due to a natural evolution of these membranes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent controlled study found that the progression of idiopathic epiretinal membrane was not accelerated in patients who have undergone phacoemulsification cataract surgery and that the visual acuity was not markedly impaired in the first year following surgery. On the basis of these results, the authors of the above study concluded that surgeons need not hesitate to perform phacoemulsification in eyes with idiopathic epiretinal membrane …”
mentioning
confidence: 92%
“…In a study, the progression of idiopathic epiretinal membrane is not accelerated by smallincision phacoemulsification cataract surgery. Furthermore, visual acuity is not impaired markedly at least for the following year (Hayashi and Hayashi, 2009). However, it is still unclear whether or not a secondary epiretinal membrane progresses after cataract surgery in eyes with other retinal morbidity such as retinal detachment surgery or retinal pathology.…”
Section: Epiretinal Membranementioning
confidence: 99%